2019
DOI: 10.1038/s41598-019-47664-w
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature catalyst based Hydrothermal liquefaction of harmful Macroalgal blooms, and aqueous phase nutrient recycling by microalgae

Abstract: The present study investigates the hydrothermal liquefaction (HTL) of harmful green macroalgal blooms at a temperature of 270 °C with, and without a catalyst with a holding time of 45 min. The effect of different catalysts on the HTL product yield was also studied. Two separation methods were used for recovering the biocrude oil yield from the solid phase. On comparision with other catalyst, Na 2 CO 3 was found to produce higher yiled of bio-oil. The total bio-oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 40 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…This makes AP a potential nutrients source for microalgae when recycled back into cultivation, which are otherwise lost. It is also reported that even harmful algal blooms are also good feedstock for HTL and AP produced is promising nutrient source for microalgae cultivation [90]. AP also has growth inhibitory compounds like phenols, amides, pyrazines, indole, metal ions like Ni etc., which either must be removed or diluted to the extent that they are no more growth inhibitory [89,91].…”
Section: Nutrient Recycling From Htl Aqueous Phasementioning
confidence: 99%
“…This makes AP a potential nutrients source for microalgae when recycled back into cultivation, which are otherwise lost. It is also reported that even harmful algal blooms are also good feedstock for HTL and AP produced is promising nutrient source for microalgae cultivation [90]. AP also has growth inhibitory compounds like phenols, amides, pyrazines, indole, metal ions like Ni etc., which either must be removed or diluted to the extent that they are no more growth inhibitory [89,91].…”
Section: Nutrient Recycling From Htl Aqueous Phasementioning
confidence: 99%
“…Naresh and Prabhakar [ 77 ], also reported the exact 20% blending of algal oil ended with better emission characteristics strikingly it has to be noted most of the research papers defends blending of diesel with 20% algal oil [ 78 ]. Biodiesel yield from N. cinta with B10 and B7 blending pattern was of good cetane value (50–51) [ 79 ].…”
Section: Unprocessed Algal Oils As Biofuelsmentioning
confidence: 99%
“…[163], Ulva sp. [164]; and a unknown mixture of algal species [165]. A detailed list of species and the catalyst studied can be found in Table 3.…”
Section: Homogeneous Catalysismentioning
confidence: 99%